2006
DOI: 10.1038/sj.npp.1301028
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase A Activity and Norepinephrine Level in Hippocampus Determine Hyperwheel Running in SPORTS Rats

Abstract: An understanding of neurological mechanisms for wheel running by rodents, especially with high exercise activity, would be applicable to a strategy for promotion of exercise motivation in humans. One of several brain regions that are candidates for the regulation of physical exercise is the hippocampus. Here we examined the running activity of Spontaneously-Running-Tokushima-Shikoku (SPORTS) rat, a new animal model for high levels of wheel-running activity, and its relation with the hippocampal norepinephrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…Further studies of activityselected lines of mice (the HR lines) and of rats bred for treadmill endurance have revealed alterations in brain function that seem to indicate changes in motivation or propensity to exercise on wheels Foley et al, 2006;Morishima et al, 2006;Belke and Garland, 2007;Keeney et al, 2008;Waters et al, 2008 Howlett et al, 2009;Meek et al, 2009;Kolb et al, 2010), including altered plasticity for some traits in the HR lines of mice (Rhodes et al, 2003b;Swallow et al, 2005;Garland and Kelly, 2006;Gomes et al, 2009). Therefore, genetic factors are known to be involved in both motivation and ability to engage in voluntary wheel running in rodents.…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 99%
“…Further studies of activityselected lines of mice (the HR lines) and of rats bred for treadmill endurance have revealed alterations in brain function that seem to indicate changes in motivation or propensity to exercise on wheels Foley et al, 2006;Morishima et al, 2006;Belke and Garland, 2007;Keeney et al, 2008;Waters et al, 2008 Howlett et al, 2009;Meek et al, 2009;Kolb et al, 2010), including altered plasticity for some traits in the HR lines of mice (Rhodes et al, 2003b;Swallow et al, 2005;Garland and Kelly, 2006;Gomes et al, 2009). Therefore, genetic factors are known to be involved in both motivation and ability to engage in voluntary wheel running in rodents.…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 99%
“…Morishima-Yamamoto et al (2005) established an original Wistar line of rats (SPORT rats) that run voluntarily 6 times longer than control rats, and the increased running is thought to result from decreases in MAO-A activity and increases in norepinephrine release in the hippocampus (Morishima et al 2006). However, in the present study, we found no evidence of hippocampal MAO-A involvement in the FSM-stimulated increases in Fig.…”
Section: Discussionmentioning
confidence: 46%
“…In rodents, acute motor activity was associated with an increased turnover of noradrenaline in the mediobasal hypothalamus [24], In a special strain of rats characterized by high motor activity elevated levels of extracellular NE were measured causing a down-regulation of alpha(2)-adrenergic receptors [36], Therefore, we had hypothesized that similar to the action of noradrenaline reuptake inhibitors, repeated episodes of noradrenergic stimulation could induce postsynaptic changes leading to decreased sensitivity for pharmacological or psychological inputs. However, the results of the present study do not support the assumption that exercise-induced downregulation of central noradrenergic neurotransmission mediates the anxiolytic and antidepressive effects of exercise.…”
Section: Discussionmentioning
confidence: 99%